Locally relevant food-based recommendations could increase iron and calcium intake for adolescent girls in Vietnam - Gie, Simone Michelle; Nguyen, Phuong Hong; Bergeron, Gilles; Tran, Lan Mai; Hoang, Nga Thu; Knight, Frances (New York Academy of Sciences, 2023)
Unhealthy eating habits are common among adolescents in Vietnam, where transitioning food environments increasingly offer energy-dense micronutrient-poor foods. Successful behavior change approaches must be feasible and acceptable, promoting local foods that are available, accessible, and preferred. Yet, few studies have investigated the potential of food-based approaches for adolescents. We used linear programming to identify problem nutrients, local nutrient sources, and realistic food-based recommendations (FBRs) to improve nutrient intake among girls 16–22 years in Thai Nguyen, Vietnam. We then identified a reduced set of FBRs to prioritize the most critical micronutrient gaps. Calcium and iron targets could not be met in any realistic diet modeling scenario. The best set of FBRs included seven recommendations which could meet intake targets for 9 of 11 modeled micronutrients. The best reduced set of three FBRs targeting iron and calcium only—although more feasible for behavior change—was less effective at improving intake of these nutrients since fewer foods were recommended. Given the difficulty of meeting calcium and iron targets using local foods within acceptable dietary patterns, additional interventions, such as supplementation, staple food fortification, or increasing the availability of affordable calcium- and iron-rich foods, may be necessary to promote dietary adequacy for adolescent girls.